2019
DOI: 10.1096/fba.2019-00068
|View full text |Cite
|
Sign up to set email alerts
|

Active site plasticity and possible modes of chemical inhibition of the human DNA deaminase APOBEC3B

Abstract: The single-stranded DNA cytosine deaminase APOBEC3B (A3B) functions in innate immunity against viruses, but it is also strongly implicated in eliciting mutations in cancer genomes. Because of the critical role of A3B in promoting virus and tumor evolution, small molecule inhibitors are desirable. However, there is no reported structure for any of the APOBEC3-family enzymes in complex with a small molecule bound in the active site, which hampers the development of small molecules targeting A3B. Here we report h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Therefore, changes surrounding the active site including variations in the arrangements of these loops are likely largely responsible for distinctions in substrate specificity, binding affinity, and deamination activity for ssDNA, as well as the physiological functions of A3s. Structural analysis using molecular modeling and dynamics simulations have been used for investigating the molecular mechanisms underlying biological functions of A3s ( 55 , 56 , 57 , 58 , 59 , 60 ). These studies have revealed the importance of active site loops in substrate binding/activity and specificity.…”
mentioning
confidence: 99%
“…Therefore, changes surrounding the active site including variations in the arrangements of these loops are likely largely responsible for distinctions in substrate specificity, binding affinity, and deamination activity for ssDNA, as well as the physiological functions of A3s. Structural analysis using molecular modeling and dynamics simulations have been used for investigating the molecular mechanisms underlying biological functions of A3s ( 55 , 56 , 57 , 58 , 59 , 60 ). These studies have revealed the importance of active site loops in substrate binding/activity and specificity.…”
mentioning
confidence: 99%
“…Though numerous other enzymes involved in various cellular and metabolic pathways have been shown to undergo such loop dynamics that can impact the accessibility of the active site [30,31], the discovery of such a state in AID represents a novel mode of regulation in DNA/RNA‐editing enzymes. This catalytic pocket duality, termed ‘Schrodinger's CATalytic pocket’, has also been reported in crystal structures and molecular dynamic simulations of APOBEC3B and has emerged as an important activity regulator across the AID/APOBEC family [32–35].…”
Section: Structural Regulation Of Mutation Catalysis By Aidmentioning
confidence: 77%
“…The previously crystallized A3Bctd-QMΔloop3 and its Arg-to-Glu or Arg-to-Ala mutants were expressed with a C-terminal 6xHis tag in E. coli strain C41(DE3)pLysS and purified as described [ 8 , 11 , 12 ]. A3A-E72A was also produced as described [ 13 ].…”
Section: Methodsmentioning
confidence: 99%